Determination of clinically appropriate flattening filter free (FFF) energy for treating lung SABR using treatment plans and delivery measurements. (16th December 2016) - Tambe, N S; Fryer, A; Marsden, J E; Moore, C; Beavis, A W
Abstract: Higher doses are delivered over a short duration for stereotactic ablative radiotherapy (SABR) and as a result individual fraction times are significantly higher compared with conventional radiotherapy. Furthermore, many lung SABR patients are elderly with associated co-morbidities and may not be able to retain their treatment position adequately. These patients benefit from faster treatment deliveries which can be achieved by using flattening filter free (FFF) beams. To determine a clinically appropriate FFF energy for accurate delivery, 15 previously delivered flattened 6 MV lung SABR plans were re-planned at 6 FFF and 10 FFF, with organ at risk (OAR) and target dose-volume statistics examined for significance. A two half arc technique, the Monitor Unit Objective Function and the AcurosXB algorithm were employed within the Eclipse TM planning system (V11, Varian Medical System). The deliverability of these FFF plans was verified by physical measurement on a TrueBeam TM (V2.5, Varian Medical System) using the Compass TM dosimetry system (V3.1, IBA Dosimetry) in addition to the usual treatment planning system comparisons. Acceptable plans were produced for all beam energies. 6 FFF provided statistically significant OAR sparing compared to 6 FF and 10 FFF. However, absolute dose differences were not clinically significant and doses were well within recommended clinical tolerances. Skin sparing was superior in the 10 FFF plans. Overall, reduction in treatment delivery time of 61% and 55% was found when using 10 FFF and 6 FFF respectively compared to 6 FF. A 15% reduction in the average treatment time was achieved with 10 FFF when compared to 6 FFF. Treatment delivery verification measurements were compared with clinically delivered 6 FF plans and no significant differences in the deliverability were seen between the plans. As a result of this study 10 FFF has been implemented for SABR lung planning locally.